Kajian Perilaku Pengguna e-Learning dengan menggunakan pendekatan Technology Acceptance Model (TAM) (Studi Kasus : e-learning Universitas Padjadjaran) - Budi Widarsa Surya; Dindin Makhmudin (STMIK Sumedang, 2019)
E-learning is believed by various parties to be effective and efficient learning media if implemented through good governance. Although some problems arise not only in terms of governance but also arise from the side of user behavior. This problem encourages experts to conduct researches that support the formation of models to measure user behavior towards the acceptance of technology, especially information technology. Models which recorded in various literature and references on results of information technology research are such as Theory of Reasoned Action (TRA), Theory of Planned Behavior (TPB), and Technology Acceptance Model (TAM). The most popular and widely used model in various studies is the TAM model that contains 3 factors which are perceived usefulness, perceived ease of use, behavioural intention to use, and 1 final factor which is actual system use. E-learning in Unpad is known as the LIVE (Learning in Virtual Environment) of Universitas Padjadjaran with the website address http://live.unpad.ac.id. This study uses the TAM model involving 3 external factors namely e-learning self efficacy, complexity and lack of time. The results showed that the factors of e-learning self efficacy, complexity and lack of time for educators are not an obstacle in the use of e-learning. This is supported by the testing result. (1) The e-learning self-efficacy factor has a significant effect on the factor of the e-learning actual system use through behavioural intention to use factor, meaning that the factor of self-efficacy influence the intention of e-learning actual system use, (2) complexity factors influences the e-learning actual system use factor through behavioural intention to use factor, which means the complexity factor influences the behavioural intention to use factor of the teaching staff to use e-learning and the last (3) the lack of time factor influences the actual system use of technology through behavioural intention to use factors, meaning that lack of time affect the behavioural intention to use of the teaching staff to use e-learning